Predicting Intention to Purchase Counterfeit Products: Extending the Theory of Planned Behavior - Patiro, Shine Pintor S.; Sihombing, Sabrina O. (International Research Journal of Business Studies, 2014)
This research was designed to test the ability of an extended theory of planned behavior (TPB) to predict purchase intention of counterfeit products. Value consciousness and past behavior are variables that added into the TPB. Three hundred and fifty respondents completed the research questionnaires. Questionnaires were distributed to respondents by email and drop-off/pick-up method. The data then analyzed using structural equation modeling (SEM). All Hypothesis were supported. This research also provides the managerial implication and suggestion for future research.